Understanding Side Hustle Intention through Skill Variety, Self-Efficacy, Expressive and Instrumental Orientation - Retno Kurniasih; Wiwiek Rabiatul Adawiyah; Achmad Sudjadi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Side hustles among academics are becoming increasingly relevant, yet research on side hustle intention in higher education remains limited, particularly regarding the roles of expressive orientation and instrumental orientation. This study aims to examine the relationships between individual skill variety, self-efficacy, and side hustle intention, while exploring the moderating effects of expressive and instrumental orientations. Data were collected cross-sectionally from 400 lecturers in Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both individual skill variety and self-efficacy positively influence side hustle intention. Additionally, expressive and instrumental orientations strengthen these relationships. The results enhance understanding of how motivational orientations support side hustle engagement and contribute to the development of models grounded in self-determination theory. The study suggests that fostering side hustles through skill development, self-efficacy enhancement, cross-functional training, mentoring, and flexible work arrangements can benefit both individuals and institutions. Moreover, promoting side ventures can generate socio-economic advantages, stimulate innovation, and inspire entrepreneurial behavior within academic communities, particularly among younger generations.